Becoming, belonging and leaving – Exit processes among young neo-Nazis in Sweden - Christer Mattson; Thomas Johansson (Journal for Deradicalization, 2018)
There is a growing field of studies on exit processes from extremist and militant organizations. At the same time, however, what is missing is a more developed oral history of exit processes in different European countries. Interviewing individuals who left the neo-Nazi movement five or ten years ago, we have studied and analyzed how the interviewees’ narratives of exit processes are re-constructed and told today. Their reconstruction of narratives and stories on the exit process was influenced by several different factors, such as the time axis, education, intimate relations, employment situation, gender, and class. The results pointed towards a number of push and pull factors. The exit processes were seldom straightforward and linear, but instead dependent upon many social-psychological factors and processes.